Angiogenesis and immune checkpoint inhibitors as therapies for hepatocellular carcinoma: current knowledge and future research directions. Issue 1 (29th November 2019) - Hilmi, Marc; Neuzillet, Cindy; Calderaro, Julien; Lafdil, Fouad; Pawlotsky, Jean-Michel; Rousseau, Benoit
Abstract : Hepatocellular carcinoma (HCC) is the second deadliest cancer worldwide, due to its high incidence and poor prognosis. Frequent initial presentation at advanced stages along with impaired liver function limit the use of a broad therapeutic arsenal in patients with HCC. Although main HCC oncogenic drivers have been deciphered in recent years ( TERT, TP53, CTNNB1 mutations, miR122 and CDKN2A silencing ), therapeutic applications derived from this molecular knowledge are still limited. Given its high vascularization and immunogenicity, antiangiogenics and immune checkpoint inhibitors (ICI), respectively, are two therapeutic approaches that have shown efficacy in HCC. Depending on HCC immune profile, combinations of these therapies aim to modify the protumoral/antitumoral immune balance, and to reactivate and favor the intratumoral trafficking of cytotoxic T cells. Combination therapies involving antiangiogenics and ICI may be synergistic, because vascular endothelial growth factor A inhibition increases intratumoral infiltration and survival of cytotoxic T lymphocytes and decreases regulatory T lymphocyte recruitment, resulting in a more favorable immune microenvironment for ICI antitumoral activity. First results from clinical trials evaluating combinations of these therapies are encouraging with response rates never observed before in patients with HCC. A better understanding of the balance and interactions between protumoral and antitumoral immune cells will help to ensure the success of future therapeutic trials. Here, we present an overview of the current state of clinical development of antitumoral therapies in HCC and the biological rationale for their use. Moreover, translational studies on tumor tissue and blood, prior to and during treatment, will help to identify biomarkers and immune signatures with predictive value for both clinical outcome and response to combination therapies.